Boundary blow-up solutions to the k-Hessian equation with singular weights. (June 2021) - Zhang, Xinqiu; Liu, Lishan
Abstract: In this paper, we discuss the k -convex solution to the following boundary blow-up k -Hessian equation with singular weights: S k D 2 u = H ( x ) u p, in Ω, u = ∞, on ∂ Ω, where k ∈ { 1, 2, …, n }, S k D 2 u is the k -Hessian operator, Ω is a smooth, bounded and strictly convex domain in R n ( n ≥ 2 ), p > 0 .